Sustainability Business Performance in Shopping-Mall in Indonesia: The Role of Ambidexterity Orientation with Mediating Effects of Strategic Flexibility and Distinctive Advantage - Alamsyah, Muhammad iqbal; Rahayu, Agus; Gaffar, Vanessa; Wibowo, Lili Adi; Triyono, Sunu Puguh; Yusoff, Yusliza Mohd (Jurnal Internasional Penelitian Bisnis Terapan, 2025)
This study investigates the factors influencing the sustainability performance of shopping malls in West Java, Indonesia, emphasizing the roles of ambidexterity orientation, strategic flexibility, and distinctive advantage. Employing a quantitative research method with a survey design, data were collected from mall managers, directors, and operational decision-makers. A structured questionnaire, based on validated constructs, measured ambidexterity orientation, strategic flexibility, distinctive advantage, and sustainability performance. The analysis used Partial Least Squares-Structural Equation Modeling (PLS-SEM) to evaluate the relationships among these variables. The findings indicate that ambidexterity orientation significantly enhances strategic flexibility, which, in turn, positively impacts sustainability performance. While ambidexterity orientation does not directly influence sustainability performance, its effect is fully mediated by strategic flexibility and distinctive advantage. Furthermore, strategic flexibility strongly contributes to developing distinctive advantages, which significantly drive sustainability outcomes. The results emphasize the importance of managerial adaptability and the strategic alignment of resources and capabilities in achieving long-term sustainability goals. This research provides actionable insights for shopping mall management, highlighting the need for innovation-driven strategies, resource optimization, and customer-centric approaches. By advancing the understanding of sustainability performance dynamics in an emerging market context, this study offers theoretical contributions and practical recommendations for enhancing competitive and sustainable operations.